2006
DOI: 10.1007/s10482-006-9106-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agave tequilana juice on cell wall polysaccharides of three Saccharomyces cerevisiae strains from different origins

Abstract: In this study, a characterization of cell wall polysaccharide composition of three yeasts involved in the production of agave distilled beverages was performed. The three yeast strains were isolated from different media (tequila, mezcal and bakery) and were evaluated for the beta(1,3)-glucanase lytic activity and the beta-glucan/ mannan ratio during the fermentation of Agave tequilana juice and in YPD media (control). Fermentations were performed in shake flasks with 30 g l(-1) sugar concentration of A. tequil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The use of commercial strains in the industrial production of traditional beverages from Latin America is a common practice to ensure fast and reproducible fermentation. The use of wine or bakery yeasts has been reported in the fermentation of agave juice to produce Tequila (Aguilar‐Uscanga et al ., ) and in the fermentation of sugarcane juice to produce Cachaça (Marini et al ., ). The use of commercial bakery or wine yeasts in the industrial production of traditional beverages results not only in lower quality products properties with less desirable sensory attributes (Marini et al ., ), but also in a modification of the yeast microbiota by means of a replacement of the native Saccharomyces strains or the formation of intraspecific hybrids between native and wine yeasts (Badotti et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of commercial strains in the industrial production of traditional beverages from Latin America is a common practice to ensure fast and reproducible fermentation. The use of wine or bakery yeasts has been reported in the fermentation of agave juice to produce Tequila (Aguilar‐Uscanga et al ., ) and in the fermentation of sugarcane juice to produce Cachaça (Marini et al ., ). The use of commercial bakery or wine yeasts in the industrial production of traditional beverages results not only in lower quality products properties with less desirable sensory attributes (Marini et al ., ), but also in a modification of the yeast microbiota by means of a replacement of the native Saccharomyces strains or the formation of intraspecific hybrids between native and wine yeasts (Badotti et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that ATJ changes the cell wall polysaccharide composition for yeast strains from different origins (bakery, mezcal and tequila) as a response to the stress caused by ATJ composition. The yeasts from tequila and mezcal are better adapted to stress than the bakery yeast (Aguilar-Uscanga et al 2007). …”
Section: Discussionmentioning
confidence: 99%